Development of biodiesel from karanja, a tree found in rural India - Sharma Y.C.; Singh B. (My University, 2025)
Development of biodiesel from karanja tree, mainly found in rural India has been investigated. The biodiesel was developed from oil expelled from the seeds of the tree. Molecular weight of the oil was determined and found to be 892.7. Both the acid as well as alkaline esterification were subsequently performed to get the final product. NaOH was found to be a better catalyst than KOH in terms of yield. Maximum yield of 89.5% was achieved at 8:1 molar ratio for acid esterification and 9:1 molar ratio for alkaline esterification, 0.5 wt.% catalyst (NaOH/KOH) using mechanical stirrer. © 2007 Elsevier Ltd. All rights reserved.